(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Workplace ergonomics is a critical determinant of the efficiency, productivity, and overall health of dental practitioners. Dentistry is inherently demanding, requiring sustained precision, prolonged static postures, repetitive movements, and high visual concentration. Poor ergonomic design in dental clinics not only increases the risk of musculoskeletal disorders among practitioners but also impacts the quality of patient care, procedural accuracy, and overall clinical performance. This article provides an in-depth review of workplace ergonomic principles, evaluates their influence on dental practitioners’ productivity and patient care quality, and explores evidence-based strategies to optimize clinical environments. It emphasizes the integration of ergonomic assessment, equipment design, workflow optimization, and practitioner education as essential components of sustainable dental practice.